2022
DOI: 10.3390/ijerph19148248
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Consumption and Associated Factors in a Population-Based Sample of 70-Year-Olds: Data from the Gothenburg H70 Birth Cohort Study 2014–16

Abstract: Older adults of today consume more alcohol, yet knowledge about the factors associated with different consumption levels is limited in this age group. Based on the data from a population-based sample (n = 1156, 539 men and 617 women) in The Gothenburg H70 Birth Cohort Study 2014–16, we examined sociodemographic, social, and health-related factors associated with alcohol consumption levels in 70-year-olds, using logistic regression. Total weekly alcohol intake was calculated based on the self-reported amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Moreover, it is important to note that mortality rate alone may not fully capture the negative health outcomes associated with alcohol consumption, as other factors also can have signi cant impact on overall well-being. For example, we have previously reported on higher rates of depression and liver disease among 70-year-olds with highest weekly consumption (41).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, it is important to note that mortality rate alone may not fully capture the negative health outcomes associated with alcohol consumption, as other factors also can have signi cant impact on overall well-being. For example, we have previously reported on higher rates of depression and liver disease among 70-year-olds with highest weekly consumption (41).…”
Section: Discussionmentioning
confidence: 91%
“…Model 3 further included somatic burden score, depression, functional independence, and self-rated health as potential mediating factors. Potential confounding factors were selected a priori based on previous literature (15,(39)(40)(41). The effect of high alcohol consumption on mortality was examined using both risk consumption (> 98 g/week) and hazardous drinking (AUDIT-C score ≥ 5 for men, ≥ 4 for women).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a previously documented systematic review by our team, it was revealed there is a strong correlation between alcohol consumption patterns and age, proximity to alcohol outlets, familial backgrounds, socioeconomic backgrounds, and religious influences [7]. Similarly, other recent records documented the social determinants of alcohol use and its consequences among communities [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 88%
“…At the first follow-up of the H70 1930 cohort in year 2005, the sample was further extended to include male and female residents in Gothenburg born on days 2, 3,5,6,11,12,16,18,20,21,24,27, or 30 of each month (except for day 27, were only those born in January-May were included).…”
Section: Methodsmentioning
confidence: 99%
“…Smoking was dichotomized as being a current smoker vs. past or never smoker. Alcohol risk consumption was defined according to the NIAAA guidelines as >98 g alcohol/week ( 16 ) and was based on self-reported alcohol consumption during the last month. Height and weight were measured, and body mass index (BMI) was calculated.…”
Section: Methodsmentioning
confidence: 99%